VARIATIONS OF PORE-WATER PRESSURE RESPONSES IN A VOLCANIC SOIL SLOPE TO RAINFALL INFILTRATION - Adrin Tohari (Indonesian Institute of Sciences, 2013)
ABSTRACT A field monitoring of hydrological response and slope movement in an active landslide area, comprising of volcanic soil, was conducted to have a better understanding of the mechanism of landslide reactivation during a rainfall period. Monitoring instruments consisted of jet-fill tensiometers, inclinometers, open stand-pipe piezometers, and a tipping-bucket rain-gauge. The records of pore-water pressure show that the hydrological responses exhibited some spatial variability, and were mainly influenced by antecedent soil moisture conditions and rainfall patterns. The ingress of wetting front was confined up to the depths of 3 m, and a transient positive pore pressure could develop at a depth of 1 m during a heavy rainfall. More sustained increase in pore-water pressure could develop at deeper soil. Meanwhile, the piezometer records show that the response of groundwater table occur more significantly in the middle and lower portions of the slope, associated with the subsurface topographical features. The analysis of antecedent moisture conditions based on the pore-water pressure measurement data indicates that simplified model of slope hydrology cannot fully explain the spatial and temporal development of the pore-water pressures observed in the soil slope